2014
DOI: 10.1093/cvr/cvu157
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial protection restores renal function in swine atherosclerotic renovascular disease

Abstract: Preservation of mitochondrial cardiolipin attenuated swine stenotic-kidney microvascular loss and injury, and improved renal oxygenation, haemodynamics, and function. These observations implicate mitochondrial damage in renal deterioration in chronic experimental ARVD, and position the mitochondria as a central therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
144
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 108 publications
(152 citation statements)
references
References 42 publications
8
144
0
Order By: Relevance
“…First, mitochondrial dysfunction in kidney cells has been implicated in the pathogenesis of CKD [3][4][5] and proposed as a therapeutic target for atherosclerotic renovascular disease. 8,17 Mitochondrial dysfunction can be a consequence of oxidative stress. 18 In functional studies, exposure to hydrogen peroxide, a reactive oxygen species, resulted in damage to the DNA replication enzyme (polymerase g) in the mitochondria and a reduction in mtDNA copy number.…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, mitochondrial dysfunction in kidney cells has been implicated in the pathogenesis of CKD [3][4][5] and proposed as a therapeutic target for atherosclerotic renovascular disease. 8,17 Mitochondrial dysfunction can be a consequence of oxidative stress. 18 In functional studies, exposure to hydrogen peroxide, a reactive oxygen species, resulted in damage to the DNA replication enzyme (polymerase g) in the mitochondria and a reduction in mtDNA copy number.…”
Section: Main Findingsmentioning
confidence: 99%
“…[3][4][5] Molecules that target mitochondrial function, including thiazolidinediones, have been proposed as therapeutic agents for protecting kidney function. [6][7][8][9] However, studies on measures of mitochondrial dysfunction and CKD at the population level have been limited.…”
mentioning
confidence: 99%
“…51 Daily subcutaneous administration of this peptide also attenuates kidney damage and improves oxygenation, suggesting that mitochondrial dysfunction may participate both in acute and chronic injury pathways in experimental ARVD (Figure 3). 52 These data suggest that targeting mitochondrial function and preventing oxidative stress injury at the time of revascularization and/or during chronic therapy may offer substantial benefit. This approach merits further study in human subjects.…”
Section: Can Injury Within the Poststenotic Kidney Be Prevented Or Rementioning
confidence: 98%
“…In a series of studies in rodent models by Szeto et al [13,15 && ], it has been shown that two agents in this class (SS-20 and SS-31) offer significant protection in AKI because of IRI, with striking positive effects on mitochondrial morphology and function, cell polarity, and overall kidney function. SS-31 (marketed as Bendavia) has also shown evidence of benefit in a larger animal model (renovascular disease in pigs) [16], and the effects in human AKI are now being investigated. Meanwhile, MitoQ, an analogue of the OXPHOS component ubiquinone (CoQ10), has been studied in a multitude of different disease processes in different organs, including in humans [17].…”
Section: Key Pointsmentioning
confidence: 99%